Análisis general del desarrollo e implementación de los mecanismos alternativos de solución de Controversias en México, de Cara al Siglo XXI - Serrano Muñoz, Lourdes Guadalupe (UNIVERSIDAD DE SONORA, 2016)
The Mexican judicial apparatus has been characterized by the resolution of conflicts in a time greater than what the society and the national economy needs. In addition, sometimes the judgments obtained are unfair to those who urged the judges. This last point is understandable, because there are no better people to comprehend a problem than those who are suffering. However, it is not what the people want.In this sense, the purpose of this essay is to briefly explain some characteristics of the main alternative dispute resolution mechanisms that are in force in Mexican legislation, as well as to emphasize the necessity and effectiveness that they promise for the future of the country.